Asynchronous point to point FSK- FM radio telemetry system with data encryption for monitoring environmental conditions / Shuhaimi Shamsuddin - Shamsuddin, Shuhaimi (2003)
Telemetry systems are an important part of communication and control technologies in today's applications such as in military, medical and environmental sciences. One of its main tasks is to acquire data at a remote location and send the data to a location either through cables or radio waves where the data can be received for analysis. The main objective of this research is to study and develop a ciphered Frequency Shift Keying - Frequency Modulation (FSK-FM) radio telemetry system for monitoring environmental conditions. The system comprises of a remote telemetry station (RTS) as a data collection center and a base telemetry station (BTS) as a data evaluation center. A software programming based on LabVIEW was developed for data processing and presentation. The data collected at RTS site are encrypted prior to transmission to the BTS by employing the One Time Pad (OTP) and Caesar Cipher algorithms. Serial asynchronous transmission was used as data communication protocol via RS232 port. Free Space Propagation, Two Ray Ground Reflection and JTC models were used to predict and compare the received power of the telemetry system. The developed telemetry system is 99 .35% accurate compared to Free Space model. The performance of the developed telemetry system is also successfully evaluated in the laboratory and field for 1000m range. The results of the evaluation show that there is no bit error during 300 and 600 bps data rates and the average SNR is 26.07 dB. The accuracy of data integrity is determined to be at 99.9945%.